RETRACTED: Quintero-Castañeda et al. Assessing Mercury Contamination Levels in the Sediments of Two Pyrenean Lakes. Diversity 2024, 16, 627 - Cristian Yoel Quintero-Castañeda; Luis Roberto Hernández-Angulo; Daniel Tobón-Vélez; Anamaría Franco-Leyva; María Margarita Sierra-Carrillo (Diversity)
The journal retracts the article, “Assessing Mercury Contamination Levels in the Sediments of Two Pyrenean Lakes” [...]